Control of engineering projects - Wearne, S. H. (Engineering management., 1989)
This is an account of the performance of three variables in the control of engineering projects - time, cost and manpower - which must be kept in harmony. It uses examples from industry to explain the selection, control and planning of a number of projects and looks at financial control.